Effects of Ionic Liquid, 1-Ethyl-3-methylimidazolium Chloride (EMIMCl), on the Material and Electrical Characteristics of Asphaltene Thin Films - Thulasiraman, S. (MDPI, 2022)
Asphaltene is a component of crude oil that has remained relatively unexplored for organic electronic applications. In this study, we report on its extraction technique from crude oil tank bottom sludge (COTBS) and its thin-film characteristics when 1-ethyl-3-methylimidazolium chloride (EMIMCl) ionic liquid (IL) was introduced as dopants. The extraction technique yielded asphaltene with more than 80% carbon content. The IL resulted in asphaltene thin films with a typical root-mean-square surface roughness of 4 nm, suitable for organic electronic applications. The thin films each showed an optical band gap of 3.8 eV and a sheet resistance as low as 105 Î©/â¡. When the film was used as a conductive layer in organic field-effect transistors (OFET), it exhibited hole and electron conduction with hole (Âµh ) and electron (Âµe ) mobilities in the order of 10â8 and 10â6 cm2/Vs, respectively. These characteristics are just preliminary in nature. With the right IL, asphaltene thin films may become a good alternative for a transport layer in organic electronic applications. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.